Pengaruh Larutan Daun Kelor terhadap Viabilitas dan Vigor Benih Padi Lewat Masa Simpan Varietas Karang Dukuh - Ria Rahmawati; Hairu Suparto; Untung Santoso (Universitas Lambung Mangkurat, 2026)
The rice plant (Oryza sativa L.) is a type of plant that produces rice. This plant is the main food source for more than half of Indonesia's population. Rice production as a food ingredient needs to be increased to meet the amount of food needed by the Indonesian population. Seeds that are stored for a relatively long time can experience deterioration (decrease in seed quality) which results in decreased seed viability. A decrease in seed quality can be seen from seed viability or seed vigor, which is initially characterized by a decrease in seed germination. Invigoration is the physical, physiological, genetic and health treatment of seeds carried out before the planting stage to increase seed viability so that the seeds are able to grow simultaneously. Moringa leaves contain natural cytokinin hormones such as isopentyladenine, dihydrozeatin, and zeatin which have the function of helping break the dormancy period by stimulating seed metabolism and starting germination, stimulating root growth by increasing The process of cell division and the specialization of cells in the roots, and this hormone also encourages cell division in the formation of shoots. This research was carried out from May to June 2024 at the Integrated Laboratory, Department of Agroecotechnology, Faculty of Agriculture, Lambung Mangkurat University. This study employed a single-factor Completely Randomized Design (CRD) with five different treatments. (1 control) which were repeated 5 times. Data analysis used Barlett's homogeneous test, Anova and DMRT advanced test. The results of the research showed that the Moringa leaf solution significantly influenced the growth rate of rice seeds through the shelf life of the Karang Dukuh variety.